A New Compact and Miniaturized GCPW-fed Slotted Rectangular antenna for Wideband UHF FIRD Applications - Rachid Dakir; Jamal Zbitou; Ahmed Mouhsen; A. Tribak; M. Latrach; A. M. Sanchez (International Journal of Electrical and Computer Engineering (IJECE), 2017)
This paper presents the development of a new miniaturized and compact GCPW-fed slotted rectangular antenna structure reader for wideband UHF RFID applications. The optimized proposed antenna is suitable to operate a large frequency-band range from 0.8GHz to 1.3GHz with a bandwidth of 500MHz with a return loss less than -10dB. The antenna is based on a 1.6mm thickness FR4 epoxy substrate with a reduce dimensions compared to the simple rectangular antenna and size of proposed antenna is 47*40mm2. The new design consists of a compact rectangular patch with symmetric U-shaped slots and I-shaped include a partial ground plan and fed by 50 Grounded coplanar line. The antenna parameters have been investigated and optimized by   using   CST Microwave Studio. To validate the CST Microwave Studio results before the   antenna achievement,   we   have   conducted another study by using ADS. The   final circuit   achieved, measured and validated. Experimental results show that the proposed antenna has good radiation characteristics and operating in UHF-RFID applications.